Daylight Performance of Fiber Optic Daylighting in Deep Plan Office Room - Felicia Ranita Angelica; Liliany Sigit Arifin; Feny Elsiana (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2023)
Most buildings have spaces far from the windows that require artificial lighting for illumination throughout the day. In fact, artificial lighting contributes to the second highest electrical energy consumption, especially in educational institutions that require more lighting. One of the appropriate solutions to illuminate areas far from windows is using a fiber optic daylighting system. FOD is used to distribute sunlight into the spaces away from the window. This research tested the lighting levels produced by alternative collector and diffuser models of FOD systems to meet the lighting level standards (lux) in discussion room P. 06. 05. Petra Christian University. This research uses experimental methods under actual weather exposure and simulation with DIALux software. Simulation results show that the room requires 6 collectors and 2 diffusers, arranged centrally and symmetrically. It produces 365 lux and a uniformity ratio of 0.59, which meets the standard. The lighting level data used was at 10:30 AM during partially cloudy conditions.